Prenatally diagnosed lower urinary tract obstruction: A 15‐year experience at two tertiary centers in Japan. Issue 9 (21st June 2021) - Sugibayashi, Rika; Wada, Seiji; Ozawa, Katsusuke; Muromoto, Jin; Oi, Rie; Yamamoto, Ryo; Ishii, Keisuke; Sago, Haruhiko
Abstract: Aim: To examine the outcomes of prenatally diagnosed lower urinary tract obstruction (LUTO) with current management using vesicoamniotic shunting (VAS). Methods: A retrospective study of prenatally diagnosed LUTO before 26 weeks of gestation at two tertiary centers in Japan between March 2002 and September 2017. LUTO was diagnosed by ultrasound demonstration of an enlarged fetal bladder associated with hydronephrosis and/or hydroureters. VAS was offered for fetuses with LUTO at ≤26 weeks of gestational age, in the presence of oligohydramnios or decreasing amniotic fluid and a favorable fetal urinary analysis. Results: Among 87 fetuses with LUTO, 46 (53%) were terminated before 22 weeks of gestation. Eight cases (9%) underwent VAS and one underwent fetoscopic urethrotomy. The live birth rates in the VAS and expectant groups were 100% (8/8) and 56% (18/32), respectively ( p  = 0.034), and the survival rates at 6 months old with a normal renal function were 38% (3/8) and 16% (5/32), respectively ( p  = 0.608). The etiology varied with six cases of associated anomalies among 23 diagnosed cases. Among the nine cases of posterior urethral valve (PUV), only one fetus underwent VAS at 25 weeks of gestation, ultimately surviving with mild renal dysfunction. Among the other eight cases of PUV that were managed expectantly, two died, and only one of the six survivors showed a normal renal function. Conclusions: More than half of the prenatally diagnosed LUTO cases were terminated. VAS seemed effective for achieving a perinatal survival, regardless of etiology. The outcomes were poor in cases of expectantly managed PUV.